1995
DOI: 10.1063/1.113394
|View full text |Cite
|
Sign up to set email alerts
|

Optimized structure for InGaAsP/GaAs 808 nm high power lasers

Abstract: The optimized structure for the InGaAsP/GaAs quaternary material lasers (λ=0.808 μm) is investigated for the most efficient high-power operation through an experiment and theoretical study. A comparative study is performed of threshold current density Jth and differential efficiency ηd dependence on cavity length (L) for two different laser structures with different active layer thickness (150 and 300 Å) as well as for laser structures with different multiple quantum well structures. A theoretical model with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…3 However, the InGaAsP/GaAs material system has small conduction-band offsets, which cause diode lasers made of such material to suffer from massive carrier leakage. As a result, one obtains a relatively high threshold-current density, J th ; 1,4,5 low internal efficiency, i ; 5,6 and low threshold-current characteristic temperature, T 0 . 5,7 A recent attempt to solve the problem of carrier leakage 8 has been the use of high-band-gap material ͑Al 0.7 Ga 0.3 As͒ for the cladding layers which delivered high T 0 , promising reliability data, but also relatively high J th .…”
mentioning
confidence: 99%
“…3 However, the InGaAsP/GaAs material system has small conduction-band offsets, which cause diode lasers made of such material to suffer from massive carrier leakage. As a result, one obtains a relatively high threshold-current density, J th ; 1,4,5 low internal efficiency, i ; 5,6 and low threshold-current characteristic temperature, T 0 . 5,7 A recent attempt to solve the problem of carrier leakage 8 has been the use of high-band-gap material ͑Al 0.7 Ga 0.3 As͒ for the cladding layers which delivered high T 0 , promising reliability data, but also relatively high J th .…”
mentioning
confidence: 99%
“…(1) The influence of immiscibility appears prominently in the LPE grown films; the growth rate drops drastically in the composition of the MG [7]. (2) The phase separation of the structure-lateral composition modulation (LCM) is induced in the epitaxial layer; the decomposition appears perpendicular to the growth direction or in the direction along the plane parallel to the growth surface [8][9][10]. These phenomena of the immiscibility have been observed in the MBE-grown InGaAsP layers; however, MBE is the most non-equilibrium growth mode of the available growth methods of InGaAsP [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, InGaAsP enables fabrication of the high performance LDs because InGaAsP is free from the Al-related problem. For example, watt-class output-power LDs have been realized by adopting InGaAsP for the active layer [1][2][3]. However, the existence of the miscibility gap (MG) is well known in a wide composition range of InGaAsP [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, 3 it was found that for InGaAsP/GaAs ͑ϭ808 nm͒ laser diodes, 300 Å is the optimal thickness for the quantum well ͑QW͒ active layer. A theoretical calculation and experimental investigation revealed that laser diodes with active layers thinner than 300 Å had a significantly larger minoritycarrier leakage to the cladding layer, degrading the threshold condition, and internal efficiency.…”
mentioning
confidence: 99%
“…Detailed fabrication procedures were reported elsewhere. 2,3,7 Laser diodes with cavity lengths varying from 200 to 2700 m were prepared without mirror coating and light-current characteristics were recorded in short pulse operation ͑pulse width 100-400 ns, repetition rate 5-2.5 kHz͒ using an integrating sphere with a Si photodiode. Figure 2 shows threshold current density ͑J th ͒ as a function of cavity length (L).…”
mentioning
confidence: 99%